Experimental investigation of control parameters for machining of copper alloys using electrochemical micromachining. (2021) - Makesh, M.; Sivaraman, G.; Saravanan, N.; Prashanth, S.; Subbiah, Ram; Anand, K.
Abstract: This work presents the machinability study of copper alloys using Electro-chemical Micro-Machining (EMM) for conicity and material removal rate (MRR). Applied voltage (AV), duty cycle (DC) and electrolyte concentration (EC) is chosen as the control parameters. Experiments trails were investigated based on L9 Orthogonal Array (OA). The mathematical equation for conicity and MRR are developed using MINITAB software. Analysis of Variance (ANOVA) is performed for finding the most significant factor. Based on ANOVA, contribution for parameters A, B, and C on MRR are found to be 60.88%, 14.40%, and 13.30% respectively. The significant factor on MRR is AV which is found to be 60.88%. For conicity, contributions of factors A, B, and C were found to be 65.54%, 18.63%, and 03.37% respectively. The significant factor on concity is AV which is found to be 65.54%.